(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The study aimed to demonstrate how the use of blockchain technology improves the transparency of financial data by providing immutable records that are visible to all stakeholders. It also explored how the application of blockchain technology increases confidence in financial data by providing independent verification mechanisms and reducing the chances of manipulation or forgery. In the practical aspect of the study, a questionnaire was distributed to employees of the Accounting and Auditing Department, assistant managers and directors at the General Company for Electrical Industries in Baghdad. Out of 100 questionnaires distributed, 89 completed questionnaires were returned, which represents a good response rate of 89%. Incomplete questionnaires were ignored to ensure data quality and validity of the analysis. The questions were carefully formulated to ensure that they reflect the important aspects of the study and are clear and understandable to respondents. The data were analyzed using SPSS V.22 statistical analysis programs. The study concluded that the application of blockchain technology in the General Company for Electrical Industries significantly enhances transparency and credibility in administrative financial reports, which contributes to improving the level of trust between stakeholders. The integrated impact of blockchain technology, in terms of data security, operational efficiency, and traceability, contributes significantly to improving transparency and credibility in administrative financial reporting. The study recommended that the General Company for Electrical Industries should be strengthened by implementing blockchain technology extensively in all its financial and administrative departments to ensure improved transparency and credibility in financial reporting. Additional resources should be allocated to train employees on the use of this technology and promote a culture of innovation in the organization.